Fraksi Heksan Daun Katuk Sebagai Obat Untuk Memperbaiki Produksi Susu, Penampilan Induk, dan Anak Tikus (HEXANE FRACTION OF SAUROPUS ANDROGYNUS LEAVES AS A MEDICINE FOR IMPROVING MILK YIELD, THE PERFORMANCE OF FEMALE, AND RAT PUPS) - Suprayogi, Agik; Kusumorini, Nastiti; Arita, Syaprianti Evi Dame (Jurnal Veteriner, 2015)
Study of Sauropus androgynus leaves fractions as a medicine for improving milk yield, the performanceof dam, and rat pups was conducted on five groups of lactating pregnant rats. Each group consists of 16rats, namely hexane fraction (FH), ethyl acetate (Fets), water (FH2O), ethanol crude extract (EEto); andcontrol group. The administration of fractions and crude extract were executed orally through feed aftereight days of mice gestation period. The average consumption dose was 57.5 mg/day, 40 mg/day, 209 mg/day, 297.5 mg/day, and 0 mg/day, respectively. The provision of treatment for 12 days gestation periodshowed no significant effect on the average daily feed intake. The FH administration did not demonstratedifferences of growth and body weight gain of dams in comparison to the control group. Whereas theadministration of FETs, FH2O, and EE to showed the growth inhibition significantly. The FH administrationshowed gradually increase of rat pups growth and body weight gain significantly in pups 7-10 days oldcompared to the control group. However, there were signs of growth inhibition on the other groups. The FHgroup revealed a positive response on the total milk yield for 10 days of lactation, compared to the othergroups. Hexane fraction has the potency as a remedy for improving milk yield without influencing the damand rat pups performance. This study also indicates side effect on growth inhibition, especially on theadministration of ethyl acetate and water fraction, and ethanol crude extract.
Keywords: Saouropus androgynus, rat, extraction, fractionation, lactation, body weight